Privatisation debates in Poland before and after communist demise: A comparative perspective - Jan Winiecki (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1991)
Poland and Hungary, the most persistent tinkerers with the Soviet economic system, became also the first communist countries to have allowed debates on the need to rearrange the structure of property rights in the economy as a way to improve its performance. Elsewhere, until the end of the 1980s, these debates were either explicitely rejected (as in Czechoslovakia or former G.D.R.) or much more limited (as in the USSR under Gorbachev). In what follows, the present writer will explain the politico-economic context, within which these debates were taking place, and will outline major options proposed there. Moving from minor to major changes formulated in the debate, I begin by presenting some proposals that kept the status of state ownership unchanged, and later evaluate further reaching ones. Also, these options, or most of them, had their predecessors in earlier debates in the West. Therefore, wherever important, linkages to these debates have been made as well.
Keywords: 330; Privatisierung; Polen